How Spaces Become Places : Place Makers Tell Their Stories - Forester, John, 1948- (Book collections on Project MUSE., 2021)
"A diverse set of place makers describe how they transformed contested or empty "spaces" into vibrant and functional "places." Spanning four countries and ten U.S. locales, these projects range from building affordable housing, to community building in the aftermath of racial violence, to the integration of the arts in community development. By recounting how they built trust, diagnosed local problems, and convened stakeholders to invent solutions, place makers offer pragmatic, instructive strategies to employ in other communities"--